Imagining Queer Methods - Brim, Matt; Ghaziani, Amin (Book collections on Project MUSE., 2019)
Imagining Queer Methods' showcases the methodological renaissance unfolding in queer scholarship. This volume brings together emerging and esteemed researchers from all corners of the academy who are defining new directions for the field. From critical race studies, history, journalism, lesbian feminist studies, literature, media studies, and performance studies to anthropology, education, psychology, sociology, and urban planning, this impressive interdisciplinary collection covers topics such as humanistic approaches to reading, theorizing, and interpreting, as well as scientific appeals to measurement, modeling, sampling, and statistics. By bringing together these diverse voices into an unprecedented single volume, Amin Ghaziani and Matt Brim inspire us with innovative ways of thinking about methods and methodologies in queer studies.